A eficácia persuasiva do discurso iurdiano: uma leitura psicanalítica - Balan, Bruna Anselmo Oliveira (2015)
The aim of this study was to investigate the effectiveness of persuasive iurdiano speech at a psychoanalytic reading. First, it described the history of Protestantism in Brazil, the origin and characteristics of the Pentecostal movement to get the understanding of neo-Pentecostalism, highlighting the Universal Church of the Kingdom of God (UCKG) as the top of the movement and therefore of great expression and interest to this study. Later, he sought to examine ways to persuade through the study of rhetoric and the understanding of how it works basically the effective religious discourse. That being said, it was possible to look into the materials gathered from various media of the universe related to the UCKG for conducting a iurdiano religious speech content analysis in order to understand the persuasive process of each content. It was suggested a triad, later thought to the analysis of the material, which is entitled as systematic persuasion strategy, aimed at a more rational aspect of the analysis. Finally, a thorough psychoanalytic reading of the triad that led us to understand that persuasion has effectiveness because it touches on the emotions of people, in addition to addressing the importance of religious experience within groups, important device in understanding the proposed theme. The speech is addressed mainly to the helpless condition clearly spelled out by Freud, making the discussion extremely current to understand the effectiveness of persuasion in every speech and possible justifications for the accession of the individual to religious discourse